Experiences of stress and anxiety related to COVID-19 preoccupation and COVID-19 difficulties among university students in North Macedonia - Angela Filipovska; Dimitrinka Jordanova Peshevska; Ana Tomovska Misoska (University American College Skopje, 2022)
COVID-19 was identified as a major public health threat to the entire population including adolescents with serious implications for their psychological well-being and mental health. The aim of the current study is to investigate the association between the COVID19 preoccupation and difficulties among university students and their mental health (anxiety and stress levels) using the biopsychosocial theoretical framework for analysis. The method was to take a convenient sample of 160 university students (61.3 per cent female and 38.7 per cent male) between the ages of 18 and 24using an online data collection form in the period September to November 2021. The instruments used were: a COVID-19 preoccupation scale; a COVID-19 difficulties scale, anxiety and stress scales from the DASS instrument. The study findings demonstrated a significant statistically positive correlation between anxiety and preoccupation with COVID-19, difficulties from COVID19, stress and being female. There is a statistically significant negative correlation with living in an urban setting. Stress is also statistically significantly positively correlated with a preoccupation with COVID-19, difficulties from COVID-19 anxiety, and being female. There is negative statistically significant correlation with living in an urban setting. The regression model statistically significantly predicted 37 per cent of the variance of the variable anxiety (F=17.71, p<.05). Experienced difficulties from COVID-19 make a significant statistically positive predictor of anxiety (Ø=.516, p<0.05), whilst living in an urban setting is a statistically negative predictor of anxiety (Ø=-.153, p<0.05).
Keywords: 330; stress; anxiety; COVID-19 difficulties; COVID-19 preoccupation; students